High-Resolution Petrographic Evidence Confirming Detrital and Biogenic Magnetites as Remanence Carriers for Zongpu Carbonates in the Gamba Area, South Tibet - Zhao, Qian; Huang, Baochun; Yi, Zhiyu; Xue, Pengfei (Frontiers in Earth Science, 2021)
Paleocene carbonates from the Gamba area of South Tibet provide the largest paleomagnetic dataset for constraining the paleogeography of the India-Asia collision in the early stage. Previous studies argued that the characteristic remanences (ChRMs) obtained from this unit were remagnetized via orogenic fluids. This study carries out a high-resolution petrographic study on the Paleocene carbonates from Gamba aiming to test the nature of the ChRMs. Electron microscopic observation on magnetic extracts identified a large amount of detrital magnetite that are multi- to single domain in sizes and nanoscale biogenic magnetite. Minor framboidal iron oxides were also identified, which were previously interpreted as authigenic magnetite that substitutes pyrite. However, our scanning and transmission electron microscopic (SEM/TEM) observations, along with optical microscope and Raman spectrum investigations further suggest that these magnetic minerals are pigmentary hematite and goethite that are incapable of carrying a stable primary magnetization. We therefore argue that the ChRMs of the limestones from the Zongpu Formation in the Gamba area are carried by detrital and biogenic magnetites rather than authigenic magnetite. The paleomagnetic data from the Gamba area are interpreted as primary origin and can thus be used for tectonic reconstructions. We emphasize that magnetic extraction, integrated with advanced mineralogic studies (e.g., electron backscatter diffraction and electron diffraction) are effective approaches for investigating the origin of magnetic carriers in carbonate rocks.